Demonstration of thin film pair distribution function analysis (tfPDF) for the study of local structure in amorphous and crystalline thin films. (2015) - Jensen, Kirsten M. Ø.; Blichfeld, Anders B.; Bauers, Sage R.; Wood, Suzannah R.; Dooryhee, Eric; Johnson, David C.; Iversen, Bo B.; Billinge, Simon J. L.
No abstract available